The Construction of a carnival costume from the Fernando Pinto’ creative process (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2023)
This article presentes considerations on the construction of a carnival costume proposed as a reinterpretation for a study on theFernando Pinto’s creative process in the plot “Como era verde o meu Xingu”, in the GRES Mocidade Independente de Padre Miguel, in 1983, from the perspective of Design, based on research carried out at the Graduate Program in Design, at the Federal University of Rio de Janeiro-UFRJ. We sougth to understand the transversalities between scenic concepts and the practice of doing in the samba school parades, from the particularities of that project to produce a comprehensive reading of the plot for viewers.
Keywords: carnival costumes; costume design; carnival fantasy; carnavalesco; thematic designer